Efficacy of adrenaline-packed dressing for bleeding control in patients undergoing cardiovascular implantable electronic device implantation; A Single-Center study. (25th November 2020) - Anusonadisai, K; Suwanagool, A
Abstract: Background: Each year, 1.65 million people around the world are implanted with Cardiac Implantable Electronic Devices [CIEDs], which our center, performed about 300–350 cases per year. These implantation process needs expertise and specializes in preventing the complication. Some complications, such as device-related bleeding complications (DRBCs) and pocket hematoma, especially in those patients receiving oral antithrombotic drugs before the surgery, should be preventable. Based on our observation of cases in the operation room, the wounds which were easily bleed can effectively create hemostasis by using adrenaline-packed dressing. The purpose of this study is to explore if the adrenaline pack dressing could reduce bleeding complications and reduce pocket hematoma in patients undergoing CIED implantation. Purpose: To evaluate if adrenaline-packed dressing during CIED implantation can demonstrate a reduction in bleeding complication. Methods: This is a single-center double-blind, randomized control study that included most of the patients undergoing CIED implantation in our center from June 2019 to Jan 2020. The patients will be randomized to adrenaline-packed dressing or matched control group. The protocol requires each patient to have a 2-weeks evaluation at the device clinic by two device-clinic staff. If DRBCs are detected, we used a caliper to measure the size in the largest dimension. Our primary outcome is the incidence of DRBCs at 2-weeks. Results: There were 165 patients enrolled from June 2019 to Jan 2020. Mean age was 73 (female 52%), 24% on antiplatelet, 36% on anticoagulant. The pocket hematoma and ecchymosis at the 2-week was 15.8% and 15.2%, respectively. The DRBCs at 2-weeks was not significantly different between groups (22.6% vs. 33.3%; p=0.125). However, the next morning hematoma was significantly decreased in the adrenaline-packed dressing group (13.1% vs. 28.4%; p=0.015). The trend of subgroup analysis in the adrenaline pack dressing group was showing a reduction of DRBCs in patients who on anticoagulation therapy. Conclusion: The adrenaline pack dressing appears to reduce early pocket hematoma significantly, but at two weeks, most of them were resolved and make no significant difference between groups. Funding Acknowledgement: Type of funding source: None